The Implications of Abortion Underground’s Institutionalization for the Management Studies - Bartosz PŁOTKA; Cristina-Iulia GHENU (Revista de Management Comparat International)
In a vast part management studies focus on the formal aspects of organizing and controlling the environment. These elements include various models of managing, types of leadership, kinds of organizational culture and so on, which are maintained, communicated and enforced within officially sanctioned channels. Their operationalizations are either direct or indirect results of the formal principles implementation, such as internal regulations, the actual law, customs, tradition, values. On the contrary, there are practices considered informal which, dependently on their social functions, may be institutionalized. An example of such a practice is illegal abortion. It engages people performing specific tasks and, in some cases, even social movements sometimes supporting the procedure which is legally dubious in some countries. The aim of this article is to investigate what do the different aspects of illegal abortion imply to the management, human resources and political studies from the perspective of informal institutions taken as theoretical category. The analyzed data comes from Polish cases of illegal abortions, demonstrating unconventional ways of managing medical personnel and preparing a background for realization of political goals.